Effect of shape and nano-segregation in Δ2-isoxazoline and isoxazole on the mesogenic behavior of 1, 3-bis-isophthalimines. Issue 5 (9th April 2022) - Merlo, Aloir A.; Gonçalves, Itamar; Lavayen, Vladimir; Livotto, Paolo R.; Weber, Caroline S. B.; Halfen, Renato A. P.; Walba, David M.; da Rosa, Rafaela R.
ABSTRACT: Bis -1, 3-isophthalimines flanked by two side 3-aryl-5-perfluoroalkylisoxazoline or 3-aryl-5-perfluoroalkylisoxazol arms were produced and liquid crystal properties were analysed. Monotropic smectic A mesophase was found for bis -1, 3-isophthalimines containing the 3-aryl-5-perfluorooctylisoxazoline (8b ). Thermal behaviour was analysed and discussed by DSC, POM, DFT calculations, cohesive energy density (CED), Hildebrand solubility parameters and molecular-shape features. Notably, for long side arm perfluorooctyl 8b, the reduced value of CED is partially compensated by molecular shape of the molecules in the condensed state favouring the SmA mesophase formation. GRAPHICAL ABSTRACT: uf0001